The Challenges of High Food and Fuel Prices - World Bank (Washington, DC, 2013)
The increase in the price of oil and food carry major adverse poverty and macroeconomic implications especially for fragile and small states and for low income households in all developing countries. In terms of their impact on income distribution, inflation, and poverty food prices are of greater and more immediate concern than high fuel prices. However, the impact of the oil price increase on economic growth is likely to be negative and the challenge of crafting appropriate policy responses to the food crisis is made much harder in a context of rising oil prices and ensuing fiscal and balance of payments pressures. This paper describes what has happened to fuel and oil prices over the past two years and links these developments to the macro-economic international context. It goes on to describe the consequences of the oil and food price increase for developing countries and especially for fragile and small states in the commonwealth. The paper also discusses policy instruments that may contribute to ameliorate the impact of the changes. Finally, it describes how the World Bank can support countries' efforts in addressing these price shocks.